2019
DOI: 10.1177/0957650919832445
|View full text |Cite
|
Sign up to set email alerts
|

Heat transfer enhancement of plate heat exchanger utilizing kaolin-including working fluid

Abstract: Plate heat exchangers having high efficiency and small size are one of the mostly used heat exchangers. They are used in many applications ranging from cooling to heating. Heat transfer improvement of plate heat exchangers can be performed using nanoparticle-including working fluids, i.e. nanofluids. Influences of kaolin-including nanofluid utilization as working fluid on heat transfer performance of the plate heat exchanger were experimentally investigated in this study. The prepared nanofluid included 2% (wt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 27 publications
0
10
0
Order By: Relevance
“…In connection with the whole uncertainties of the measured data taken into account, it is clearly observed that their values were acceptable (acceptable interval is 0%–2%) (Sözen et al , 2019b). Experimental results’ uncertainty was calculated by considering the divergence in values.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In connection with the whole uncertainties of the measured data taken into account, it is clearly observed that their values were acceptable (acceptable interval is 0%–2%) (Sözen et al , 2019b). Experimental results’ uncertainty was calculated by considering the divergence in values.…”
Section: Methodsmentioning
confidence: 99%
“…In this regard, as thermophysical properties of the working fluid get higher, thermal performance can be enhanced at the same time. Nanofluids or nanoparticles-containing working fluids have been used as working fluid in recent years owing to their upgraded properties such as thermal conductivity, heat transfer capability and viscosity in many thermal energy conversion systems varying from heat pipes (Tsai et al , 2004; Kang et al , 2006; Kang et al , 2009; Lin et al , 2008; Sadeghinezhad et al , 2016; Gupta et al , 2018; Sözen et al , 2019a), plate heat exchangers (Khanlari et al , 2018; Sözen et al , 2019b; Ozdemir and Ergun, 2019; Variyenli, 2019), solar energy systems (Kaya et al , 2019; Yousefi et al , 2012; Kiliç et al , 2018; Dehaj and Mohiabadi, 2019) and even in compression-ignition engine (Ağbulut et al , 2020). Accordingly, nanofluids have been successfully used for improving the thermal performance of boiling–condensation processes.…”
Section: Introductionmentioning
confidence: 99%
“…Aydin et al [8] used Triton X-100 and Sodium Dodecyl Benzene Sulfonate surfactants to stabilize Bauxite-water nanofluids and found 20.9% enhancement in heat pipe efficiency with SDBS surfactant. Sozen et al [9] used kaolin nanofluid in heat exchanger and found 9.3% enhancement in heat transfer coefficient. Emine et al [10] CuO+Al2O3/water hybrid nanofluid in a U-type tubular heat exchanger and found 12% enhancement in heat transfer coefficient at 1% concentration.…”
Section: Introductionmentioning
confidence: 99%
“…), a base fluid in which nanoparticles are doped and a surface-active agent (surfactant) to prevent agglomeration of nanoparticles. It was observed in latest studies that nanofluids have been successfully employed as working fluid in various systems (Chen et al 2013, Ghanbarpour et al 2015, Kim and Bang 2015, Sözen et al 2016, Khanlari et al 2019, Baïri and Laraqi 2019, Ozdemir and Ergun 2019, Dagdevir et al 2019, Sözen et al 2019a, Sözen et al 2019b) more in particular in heat pipes (Huminic and Huminic 2013, Venkatachalapathy et al 2015, Tharayil et al 2015, Sözen et al 2018, Gürü et al 2019. To illustrate; Hassan et al (2015) analysed influence of accumulation on the heat pipe wick porosity following the alumina (Al2O3) nano fluid usage as the working medium.…”
Section: Introductionmentioning
confidence: 99%